Persoalan Kriteria Batasan Pertanggungjawaban Pidana Korporasi: Tinjauan Terhadap Peraturan Mahkamah Agung Nomor 13 Tahun 2016 - Nur Aripkah (Fakultas Hukum Universitas Islam Indonesia, 2020)
The formulation contained in Article 4 paragraph (2) of Supreme Court Regulation (Perma) No. 13 of 2016 concerning Procedures for Handling Criminal Cases by Corporations, especially those related to the element of determining errors in corporate criminal liability, still creates confusion and legal debate in it. As in addition to the element of actus reus (action) which is synonymous with criminal responsibility, there is an element of mens rea (error) which is also very essential and closely related to criminal liability. Thus in this research the study is focused on the problem of the criteria for limiting corporate criminal liability in accordance with Perma No. 13 of 2016 and the theory of corporate criminal responsibility contained in the Perma. The research method used is normative with a statutory, conceptual, and case approach. In the research it was found that the problem of the criteria for limiting corporate criminal liability as stipulated in Perma No. 13 of 2016 lies in the unclear and non strict standards of the criteria to regulate corporate criminal liability and this issue can be viewed from the vicarious liability theory and corporate culture model theory.